Kejadian Luar Biasa Keracunan Makanan Pada Acara Perayaan Ulang Tahun di Desa Karoya Kecamatan Cipicung Kabupaten Kuningan: Studi Kohort Retrospektif - Cecep Heriana; Ucup Supriatna; Maulia Awangga; Wardoyo . (Jurnal Ilmu Kesehatan Bhakti Husada: Health Sciences Journal, 2015)
Introduction : Food poisoning is a public health problem in Indonesia. During the years 1997-2001 there were 189 times the reported outbreaks of food poisoning. Kuningan regency is one area that is often experienced outbreaks of food poisoning. On February 20, 2014, food poisoning outbreak had occurred on the children’s birthday party in Kuningan. The investigations were conducted to obtain information about transmission source and risk factors affecting the outbreaks. Methode : The study design were descriptive and analytic with Retrospective Cohort design. Ill subject is defined as people who consume food derived from children’s birthday party and have clinical symptom of food poisoning. Healthy subject is defined as people who consume food derived from recitation activity, but no clinical symptom of poisoning. Statistical test used was Chi-square (bivariat). Results: The number of food poisoning case were 87 with dominant clinical symptoms: 100% Vomiting, Nausea 77.01%, 42.52% Headache, Diarrhea 29.88%, 11.49% Fever. The shortest and longest incubation periods were 1 and 11 hours. The highest attack Rate (AR) of the food in case group was rice (92.3%), Statistical analysis showed that risk factors related to food poisoning outbreak were consuming rice cake (p-value: 0,0001; RR: 1,62). Laboratory result indicated that there were Escherichia Coli bacteria in rice and mie. Conclusion: Food poisoning outbreak was caused by rice cake which was contaminated by Escherichia Coli bacteria. Recommendation given to was rice and mie producer were separate cooking place with cleaning place of rice and mie, and distribute rice and mie as soon as cooked and do not use well water for cooking To health department, always water quality monitoring wells and train food hygiene-sanitation a to informal food producer, and crosssectoral cooperation on prevention of poisoning